LET’S PLAY A GAME: GO IN SERBIA - zhou, guanwen (Sport - nauka i praksa, 2026)
This paper systematically reviews the development of the game of Go in Serbia from 2016 to 2025, based primarily on publicly available data from the European Go Database. It provides a descriptive analysis of the current situation with the game of Go in Serbia. The findings indicate that while the number of Go players in Serbia is relatively small compared to some larger European countries in terms of economy and population, it ranks second among the nations of former Yugoslavia, following only Croatia. The cities of Niš, Belgrade, and Kragujevac have seen the greatest development of the game of Go in Serbia. Niš, as the city with the highest level of popularization, already has three elementary schools committed to offering Go as an extracurricular activity. Serbian players are also actively engaged in exchanges with players from neighboring countries and frequently compete in various open tournaments. Moving forward, the development of Go in Serbia should involve continuing to treat schools as a key platform for promotion, which will require collective participation and long-term investment of multiple stakeholders.